DESIGN OF E-COMMERCE DISTRO USING RAPID APPLICATION DEVELOPMENT (RAD) MODEL - Apriade Voutama; Garno Garno; Agung Susilo Yuda Irawan; Elfina Novalia (Kresnamedia Publisher, 2022)
Information technology is developing so rapidly that it has become a significant need in all fields. One is in the Business of buying and selling clothes at the Celsius distribution. Sales are still carried out traditionally or using less good places for distribution because they rely only on customers who come to the store, so the innovation of online sales technology or e-business is needed. The creation is to build e-commerce as a medium for buying and selling online with a broader market coverage. E-commerce is a system designed to process goods and services' buying, selling, and marketing through an electronic system. They built this e-commerce using UML (Unified Modeling Language) and PHP-MySql programming language. Some UML diagrams are used, such as Usecases, Activity Diagrams, Sequence Diagrams, and Class Diagrams, and assisted with interface design before being translated into applications. Its e-commerce is built into two parts: the admin panel and the user panel on the system, where this e-commerce is based on a website. The admin panel is managed by the section owner as the manager of online sales management, while the board is the system user who makes transactions from the system. The tests involve random owners and users to get responses to the e-commerce so that they are implemented on an ongoing basis.